Efektivitas Edukasi Permainan Ular Tangga terhadap Peningkatan Pengetahuan dan Tindakan Memakai Masker dan Mencuci Tangan pada Anak selama Pandemi Covid-19 - Apriliana Afghani; Ennimay; Eka Wisanti (Journal of Bionursing, 2022)
Education to prevent the spread of Corona Virus Deases 19 in children is urgently needed. Efforts to increase children's knowledge and action in preventing COVID-19 can use media that are interesting and fun like snake and leadder game. This study aimed to determine the effectiveness of education using snake and ladder media on the knowledge and action of wearing masks and washing hands in children during the COVID-19 pandemic. The research design was pre-experimental with the type of One-group pretest-posttest design. Total 38 children recruited by simple random sampling technique partisipated. The research instrument used a questionnaire sheet. Data analysis included univariate and bivariate analysis with paired t test Results showed that there were differences in the average knowledge and action of respondents before the study was carried out, which increased after education using snakes and ladders media was p value 0.001. It concluded that education using media snake ladder game improved respondent knowledge and behavior. The study finding suggested that every person who want to educate children can use the snake and ladder game as a medium to iinprove their knowledge and behavior.